Direct Somatic Cell Reprogramming: Treatment of Cardiac Diseases - Guo, Chuner; Patel, Kishan; Qian, Li (Current Gene Therapy, 2013)
Cardiac diseases are the major causes of morbidity and mortality in the world. Cardiomyocyte death is a common consequence of many types of heart diseases and is usually irreversible. Scar tissues formed by cardiac fibroblasts serve compensatory roles for the injured heart but eventually weaken cardiac function and result in life-threatening heart failures. Unfortunately, adult human hearts have limited regenerative capacities. In the past decades, many interventional approaches have been taken in an attempt to restore functional cardiomyocytes in an injured heart. Promising advances have been made in directly reprogramming mouse fibroblasts into cardiomyocyte-like cells both in vitro and in vivo. Recently, several different methods have been reported, including the use of transcription factors and microRNAs. In addition, two in vivo studies showed heart function improvements with delivery of reprogramming factors in mouse infarcted hearts. Although many of these studies are at early preliminary stages, the plausibility of applying cardiac reprogramming on patients for regenerative purposes is exciting, and may lead to numerous novel research directions in the field. This review will discuss the history, recent advances and challenges of cellular reprogramming, specifically in the field of cardiac regeneration.
Keywords: fibroblasts